PENERAPAN SANKSI PIDANA DAN TINDAKAN TERHADAP ANAK MENURUT UU NO. 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Andhik Eko Susanto (Universitas Islam Kadiri, 2022)
Sanction fallout represent the power appliance to strengthen to to go into effect a norm and to prevent and also fight against the action bothering to go into effect a norm. Target which wish reached from sanction fallout to child to be the child can be mixed return to society. Double Track system represents the system two band concerning sanction in criminal law that is sanction of crime and type of action sanction. Even if in practice, difference between sanction of crime and action sanction often rather hazy, but elementary idea storey; level both owning elementary difference, whereabouts crime sanction coming from the elementary idea